Determinan Perilaku Suami yang Mempengaruhi Pilihan Penolong Persalinan bagi Istri - Sodikin Ova Emilia, Koentjoro (Berita Kedokteran Masyarakat (BKM), 2009)
Background: Culture often gives  limitation  for women  in decision  taking  regarding  their health.  In  fact, husbands play an  absolute  role  to determine who will  attend and  help  the  delivery.Objective: To  explore  husbands’  behavior  in  choosing and  determining  that will  help  their wife’s  delivery.Methods: This  is  a  survey study  using  cross-sectional design. The samples were  110  husbands who had  a wife  delivering  in Pekuncen  Sub District’s  primary  health  center, Banyumas District, Central  Java, during  the period of  1 January  2005 –  31 December  2005.Results:  The  variables  that  had  significant  relationship  in  choosing  and  determining  birth  attendant were husbands’ education OR  =  7.57  (95% Cl: 2.11  – 27.15),  delivery cost OR =  6.77  (95% Cl: 2.06  – 22.28)  and husbands’  trust OR = 0.15  (95% Cl: 0.04 – 0.55). Husbands with higher  level of education had an opportunity of 7.5  times  increased  to choose and determine  the birth attendant compared  to  those with  lower  lever of education. Husbands’  trust had  an opportunity of 7  times decreased  to choose and determine  the  birth attendant compared to those with no trust to the birth attendant. Expensive delivery cost would be 6.7 times increased the determination of  the birth  attendant by  health provider  compared  to  cheap  delivery  cost.  It was  because  of some  additional cost  for  the  health  provider  that was  relatively  high. As  a  result, mean distribution  curve of  the birth  attendant cost would  tend  to go  to  the  right.Conclusions: Husbands’  education,  cost,  and  trust  factors were  the  determinant  factors  in choosing  and determining who would  attend  the  delivery.Keywords:    health  reproduction,  husband,  determining  of  child-birth  assistant